2008
DOI: 10.1002/macp.200700584
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Water in PEO‐Based Segmented Block Copolymers and its Effect on Transition Temperatures

Abstract: The effect of water on block copolymers that contain hydrophilic PEO flexible segments is studied. The polyether phase consisted of either PEO or mixtures of PEO and hydrophobic PTMO, monodisperse crystallisable T6T6T was used as hard segments. Water absorption as a function of relative humidity and PEO content were studied. The PEO melting temperature and crystallinity were strongly reduced when the copolymer absorbed water, while the PTMO phase remained unaffected by its presence. Freezing water was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…At heating rates typically used in DSC scans (10 °C /min), free water shows a broad melting peak that starts at 0 °C and is centered at ~ 5 °C. At cooling rates of 10 °C/min used in this study, which are typical, the free water supercools and freezes at ~ −20 °C [11, 49]. Such sharp freezing exotherm and broad melting behavior for water was seen in all of our samples with at least ~ 1 wt % water.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…At heating rates typically used in DSC scans (10 °C /min), free water shows a broad melting peak that starts at 0 °C and is centered at ~ 5 °C. At cooling rates of 10 °C/min used in this study, which are typical, the free water supercools and freezes at ~ −20 °C [11, 49]. Such sharp freezing exotherm and broad melting behavior for water was seen in all of our samples with at least ~ 1 wt % water.…”
Section: Resultsmentioning
confidence: 75%
“…The influence of PEG depends on whether the polymer is a blend [56], a graft [1, 7], a diblock [810] or a segmented block [11] copolymer. Segmented block copolymers with PEG as one the blocks have been studied in aqueous solution [1214], gel [15], and in the solid phase [10, 1617].…”
Section: Introductionmentioning
confidence: 99%
“…These discrete domains could be the precursors of the water channels that facilitate the erosion of the polymer. An AFM study of the morphology in a segmented block copolymer with PEG as one of the blocks in a chain of crystallizable tetra-amide segments showed that the polymer swells inhomogeneously and the surfaces have 10–50 nm high and 100 nm wide clusters [33]. In our study the PEG is incorporated into a noncrystallizable main-chain, and shows much smaller hydrated clusters.…”
Section: Resultsmentioning
confidence: 58%
“…This scattering arises from the fluctuations in the distribution of water at 10 –100 nm length scale. These fluctuations could be in the form of clusters, domains or networks of water shown schematically in the inset to the figure [3637]. The q -range of these plots suggests that the length scale of these structures is 10–100 nm.…”
Section: Resultsmentioning
confidence: 99%